Fortifying the Mutilated: A Case Report on Anatomical Dentin Post - Mrinal Nadgouda; Aditya Patel; Manoj Chandak; Swayangprabha Sarangi; Saee Wazurkar (Journal of International Clinical Dental Research Organization, 2025)
Biological dentin posts are a novel approach to restorative dentistry that capitalizes on the natural compatibility of dentin with the surrounding biological tissues. Dentin posts are made from human dentin and are designed to mimic the natural structure of teeth. The aim of this study was to restore badly mutilated teeth using posts made from dentin which helps to integrate the dentin with the host tissues, reducing the risk of side effects or foreign body reactions. This study cumulates three cases which have successfully salvaged an unsalvageable tooth to restore strength and functionality in the oral cavity. In this case, a 42-year-old woman complained of broken teeth in the anterior maxillary region of the jaw. On radiographic evaluation, adjacent tooth was badly mutilated hence, treatment plan was devised to procure the palatal root for postcustomization to be cemented in the affected tooth. On taking radiographic as well as clinical follow-up, no further damage to the periodontal apparatus was seen. Furthermore, the prosthesis delivered catered to the patient’s standard way of life. This case report enlightens clinicians to restore a balance between conservative fortification of severely damaged teeth aiming to preserve occlusal harmony and proprioception leading to a holistic approach in achieving superior dental care. Dentin posts have excellent biocompatibility, allowing for long-term stability and successful osseointegration of restorative materials. In addition, the mechanical properties of dentin posts are similar to natural teeth, providing a favorable elasticity modulus that reduces the stress concentration and the risk of fractures. In conclusion, biological dentin posts are a revolutionary development in restorative dental care that combines biocompatibility with mechanical integrity and versatility.